(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Fungi produce secondary metabolites with insecticidal properties. To investigation the insecticidal activity from the isolation of secondary metabolites in fungus, Penicillium pinophilum and their toxicity against cowpea weevil, Callosobruchus maculatus. Pure fungi cultures were grown in small scale on PDA for two weeks. The fungi grown on PDA were used for further investigations and grown in large scale. After extracted to EtOAc and isolated bioactive compounds. The bioactive EtOAc extracts were partitioned with hexane, CHCl3 and 50 % MeOH and bioactivity of the three fractions (hexane fraction, chloroform fraction and 50 % MeOH fraction) were evaluated for bioactivity separately using the insecticidal bioassay (Residual Film Bioassay) and anti-inflammatory bioassay (Heat Induced Human Red Blood Cell Bioassay). After bioactive CHCl3 fraction and it sub-fractions were further purified using column chromatography and preparative TLC respectively. Pure compound 3 isolated from the chloroform extract of P. pinophilum was shown highly % mortality values (lowly LD50 values) and pure compounds 1, 2 and 3 were shown highly % inhibition values for above bio assays respectively. So results suggest pure compound 3 can be used as bio-insecticide against C. maculatus and pure compounds 1, 2 and 3 better than that aspirin as antiinflammatory drugs.